Determinan Kepuasan Nasabah Pada Bank Syariah Indonesia - Eri Supra; Decky Hendarsyah (el-Jizya : Jurnal Ekonomi Islam, 2022)
This research aims to show service quality, internet banking, trust, and accessibility partially or simultaneously on customer satisfaction at Bank Syariah Indonesia Bengkalis sub-branch office. This research was built using a quantitative descriptive approach based on primary and secondary data in questionnaires and library literature. The population of this research is customers of the Bank Syariah Indonesia Bengkalis sub-branch office. Sampling using random sampling technique with a total sample of 98 people. Data analysis used multiple linear regression, previously tested using validity, reliability, and normality tests. This research shows that service quality, internet banking, trust, and accessibility have a positive and significant impact on customer satisfaction at the Bank Syariah Indonesia Bengkalis sub-branch office. Simultaneously, service quality, internet banking, trust, and accessibility significantly affect customer satisfaction at the Bank Syariah Indonesia Bengkalis sub-branch office.